MANUFACTURE OF CHEMICAL UNO SPIN LEARNING MEDIA ON ELEMENTS PERIODIC SYSTEM MATERIALS - Siti Halimatusya’diah; Imelda Helsy; Sari Sari (Gunung Djati Conference Series, 2021)
This study aims to describe the appearance of chemical uno spin learning media and analyze the results of the validation test of chemical uno spin learning media on the elemental periodic system material. This research method uses the Design Based Research (DBR) method. Flowcharts and storyboards contain the stages of making chemical uno spin media including media design, media components and rules for using chemical uno spin media. The uno spin chemistry learning media is expected to be a tool in the learning process regarding the periodic system material through educational and challenging games. Then the validation test was carried out on three validators, namely media experts, learning experts and content experts. The validation result data shows a value of 0.89, which indicates that the uno spin chemical media is valid and can be used as a tool in the learning process of the element periodic system material.